2007
DOI: 10.2170/physiolsci.rp013006
|View full text |Cite
|
Sign up to set email alerts
|

ROS Scavenging Activity and Muscle Damage Prevention in Eccentric Exercise in Rats

Abstract: Depending on intensity, eccentric exercise is experimentally and clinically documented to have opposing dual effects on skeletal muscle; intense eccentric exercise damages muscle, but daily low-load eccentric exercise prevents damage. To clarify the mechanisms of this dual effect, microscopic damage and oxidative stress were studied in rat quadriceps muscle. Oxidative stress was estimated from an immunostaining of advanced glycation end-products (AGE) and a measurement of muscle tissue preparations, the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…In experiments that we have conducted on rats, we have studied muscle damage and its prevention by making rats perform the eccentric exercise of running downhill. Maruhashi [16] showed that 1 day after a high-intensity eccentric exercise, reactive oxygen species (ROS) were found in the muscles, and that 2-3 days later, evidence of muscle damage was found. These results suggested that ROS is associated with microscopic muscle damage resulting from high-intensity eccentric exercise and that ROS can cause muscle damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experiments that we have conducted on rats, we have studied muscle damage and its prevention by making rats perform the eccentric exercise of running downhill. Maruhashi [16] showed that 1 day after a high-intensity eccentric exercise, reactive oxygen species (ROS) were found in the muscles, and that 2-3 days later, evidence of muscle damage was found. These results suggested that ROS is associated with microscopic muscle damage resulting from high-intensity eccentric exercise and that ROS can cause muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms seem to be involved in the process of producing the repeated bout effect, but it remains unclear how the mechanism of low-load eccentric training is involved. Maruhashi [16] reported that when low-load eccentric training is conducted beforehand, the initial subcellular damage that triggers subsequent ROS production 1 day after high-intensity eccentric exercise is inhibited; as a result, secondary muscle damage is prevented. In the current study, we used the same exercise protocols to burden rats with low-load eccentric training and highintensity eccentric exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contradictory results of these previous studies might be due to differences in the timing and methods used to measure SOD activity, differences in the exercise training protocols, or differences in the fiber composition of the muscles investigated. Maruhashi et al [35] used the same exercise protocol and technique to assay ROS scavenging activity as in the present study; they reported that low-load eccentric training prevented intense eccentric exercise-induced muscle injury not through elevated ROS scavenging activity, but through a suppression of initial subcellular damage that triggered subsequent inflammatory cell infiltration and ROS production. Since the present study showed that HS has the ability to increase ROS scavenging activity, there is a possibility that it also has a distinct mechanism to prevent exercise-induced muscle injury compared to lowload eccentric training.…”
Section: Discussionmentioning
confidence: 78%
“…Detailed mechanisms underlying this dual effect have not yet been fully studied experimentally (36,37). Vissing et al (38) showed that this heat shock protein response to eccentric exercise was concurrently attenuated with attenuation of muscle damage when eccentric exercise was repeated 8 weeks later.…”
Section: Discussionmentioning
confidence: 99%